The Relationship between Domain Analysis and Knowledge Maps in Knowledge Organization: An Analytical Study (The International Journal for Scientific Research, 2026)
This study aimed to identify the relationship between domain analysis and knowledge maps in knowledge organization by explaining the concept of domain analysis, its types, techniques, construction steps, and role in knowledge organization, as well as the concept of knowledge maps, their benefits, techniques, construction steps, and role in knowledge organization. The study adopted the descriptive-analytical approach and content analysis for examining the relevant scholarly literature in order to extract the main concepts and develop a theoretical framework explaining the relationship between domain analysis and knowledge maps. The study found that domain analysis contributes to understanding the conceptual structure and semantic relationships within knowledge domains and that knowledge maps represent a supportive tool for representing these concepts and relationships within a visual or networked structure. The findings also revealed that the relationship between domain analysis and knowledge maps is complementary, based on the transition of knowledge from the stage of understanding and analysis to the stage of representation and organization, thereby supporting the semantic organization of knowledge and the development of ontologies and intelligent systems within knowledge organizations.
Keywords: Domain Analysis; Knowledge Maps; Knowledge Organization